2001 Volvo Award Winner in Basic Science Studies: Effect of nutrient supply on the viability of cells from the nucleus pulposus of the intervertebral disc. - Horner, H; Urban, J (2001)
STUDY DESIGN: Disc cell viability was analyzed in relation to nutrient supply and cellular demand in vitro in a diffusion chamber. OBJECTIVE: To determine relations among nutrient supply, nutrient concentrations. and cell viability. SUMMARY OF BACKGROUND DATA: Although a fall in nutrient supply has long been thought the cause of disc degeneration in vivo, little information exists about the effects of nutrient levels or supply on cell viability and metabolism. METHODS: Isolated bovine nucleus cells were cultured in agarose gels in a diffusion chamber up to 13 days. Nutrients were supplied to the open sides of the chamber and diffused through the gel to the center, 12.5 mm away from the nutrient supply, in a configuration analogous to that of the disc in vivo. Profiles of cell viability and concentration of glycosaminoglycans across the chamber were measured in relation to cell density and medium composition. RESULTS: Cells remained viable across the chamber at low cell densities. However, at higher densities, cells in the center of the chamber died. The viable distance from the nutrient supply fell with an increase in cell density. Glucose was a critical nutrient. Survival was also poor at acidic pH (6.0). At 0% oxygen, disc cells survived up to 13 days with no loss of viability, but produced very little proteoglycan. CONCLUSIONS: The results support the idea that maximum cell density in the disc is regulated by nutritional constraints, and that a fall in nutrient supply reduces the number of viable cells in the disc and thus leads to degeneration.